The mediating effect of company value from risk management, direct investment and taxation on economic growth - Paulus Johan Lolo (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Indonesia's fuel consumption level is experiencing fluctuating changes following the dynamics of world crude oil supply and demand conditions and geopolitics. This research aims to analyze and discover the direct and indirect influence of risk management, direct investment, and taxation on company value and economic growth as a useful research contribution for those interested. A complete sampling of 251 companies in South Sulawesi was determined using data pooling techniques between cross-sections and time series. Data were analyzed using the Structural Equation Model using the AMOS program. The research results found that risk management and investment have a direct positive and significant effect on company value, which means that risk management and company investment determine the achievement of company value. Taxation has an insignificant positive influence on company value, which means that implementing the tax system determines the achievement of company value. Risk management, investment, and taxation directly have a positive and significant influence on economic growth, meaning that risk management, investment, and taxation will support increased economic growth. Company value has a significant favorable influence on economic growth, which shows that the better the company value, the more influence it has on increasing economic growth.